Perceptions of hip-hop dance. - Swee, Daren Jin Quan. (2011)
In order to better understand the glocalization of hip-hop dance from the perspective of the user, the present study started off with a qualitative study by interviewing dance instructors from both the U.S and Singapore to gain insights on the cultural meanings of hip-hop. This was followed by a quantitative study in which the participants were given 5 sets of questions, assessing their perception of hip-hop, Singapore culture, U.S culture, their motivations behind dancing hip-hop, and the importance they attached to certain aspects of the dance. Hip-hop dance was likely to be perceived as similar to the Singapore culture as compared to the U.S culture. In addition, there was high possibility that extrinsic motivation (vs. intrinsic motivation) of the dancer would lead dancers to emphasize on the extrinsic (vs. intrinsic) aspects of the dance. Lastly, findings also supported the hypothesis that dancers who perceive hip-hop to be more similar to the host culture as compared to the local culture, will emphasize the intrinsic aspects of the dance.